Temperature and time dependence of electrical and mechanical durability of LDPE/diamond composites - Boydag, FS; Özcanli, YL; Alekberov, VA; Hikmet, I (ELSEVIER SCI LTD, 2006)
In this study, the dependence of the electrical (tau(E)), mechanical (tau(sigma)) life time on electrical strength (E) and mechanical tension (sigma) of low density polyethylene composites with commercial diamond additive (LDPE/diamond) at different temperatures are investigated and compared with those of pure LDPE. 50-100 mu m thick samples with the additive amount varying between 0.1-3% were prepared by using hot pressing method. log tau(E) -f(E, T), E versus diamond additive percentage are drawn and the determined values of mechanical degradation parameters at constant temperature are listed. Since tau(E) and tau(sigma) both depend on temperature, electrical degradation mechanism is similar to the mechanical one proving the validity of the thermofluctuation theory. The results indicate that E and sigma values reach maximum for 0.5% diamond and are equal to 8.5 x 10(7) V/m (6.0 x 10(7) V/m for pure LDPE) and 82 MPa (68 MPa for pure LDPE), respectively which complies with our other studies. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: polymer-matrix composites (PMCs); electrical properties; mechanical properties; strength; POLYMER COMPOSITES; POLYPROPYLENE; FILMS; PP; Engineering; Materials Science